Biopesticides in organic farming : recent advances - Awasthi, L. P. (Boca Raton, FL : CRC Press, 2021)
"The book entitled "Biopesticides in Organic Farming : Recent Advances", describes critically reviewed, key aspects of organic farming and provides a unique and timely science-based resource for researchers, teachers, extension workers, students, primary producers and others around the world. This book is intended to be a unique and indispensable resource that offers a diverse range of valuable information and perspectives on biopesticides in organic agriculture. It has chapters on each and every aspect related with biopesticides in organic farming which are compiled by researchers and eminent professors at various universities across the globe. The wide spectrum information in various chapters with the addition of the terms related to organic farming and concept statements is presented in very concise manner. Features: This book is designed, as per course curriculum of different universities offering courses on Organic Farming, for undergraduate and post graduate students, researchers, university professors and extension workers. The first section provides, Overview of organic farming with special reference to biopesticides followed by the Principles of the applications of biopesticides in organic farming, Impact of Environmental factors on biopesticides in organic farming, Pesticides Exposure Impacts on Health and Need of Biopesticides in Organic Farming, and Role of nutrients in the management of crop diseases through biopesticides. The next section deals with the management of various crop diseases through biopesticides of bacterial, fungal, viral, and Insect sex hormone, Natural enemies and Integrated Pest Management, Biotechnological Trends in Insect Pests Control Strategy, Challenges in the popularization of Biopesticides in organic farming, Certification process and standards of organic farming and Marketing and export potential of organic Products. Information presented in an accessible way for students, professors, researchers, business innovators and entrepreneurs, management professionals and practitioners"--
Overview of organic farming with special reference to biopesticides -- The principles of the application of biopesticides in organic farming -- Impact of Environmental factors on biopesticides in organic farming -- Opportunities and challenges in the application of biopesticides in organic farming -- Impact of crop protection strategies with biopesticides in long sustainable organic agriculture -- Strategies for the application of biopesticides in crop protection -- Pesticides exposure impacts on human health and need of biopesticides in organic farming -- Microbial agents as biopesticides for nutrient management in organic agriculture -- Bacillus thuringiensis: characterization of new strains and use as bioinsecticide to Spodopterafrugiperda (Lepidoptera: Noctuidae) in southern Brazil -- Management of fungal diseases of chickpea (Cicer arietinum L) through plant growth promoting actinobacteria and their secondary metabolites -- The role of plant growth promoting bacteria in sustainable plant disease management -- Killing bacteria as agents of insect pests control -- Biological control of pests using Bacillus thuringiensis -- Crop protection through fungal bio-pesticides -- An endeavor of modern organic agriculture -- Management of the diseases vegetable crops through fungal Bio-pesticides -- Usage of Entomopathogenic viruses for insect pests control -- Viral biopesticides : an ecofriendly nonchemical approach for the management for insect pests in crops -- A modern weapon in organic agriculture -- Management of crop diseases through viral Bio-pesticides -- Crop disease control through application of algal Bio-pesticides -- alternate route map in organic farming -- Entomopathogenic protozoa roles in the management of insect pest populations -- Protozoan bio-pesticides: A new horizon in organic farming -- Management of fungal diseases of crops through plant based natural products and biopesticides -- Management of fungal diseases of crop plants through biopesticides -- Management of bacterial diseases of crops through plant-based natural biopesticides -- Management of insect pests of Cola nitida and C. acumunata Schott and Endl Nuts (Balanogastris kolae and Sophrorhinus spp (Coleoptera: Curculionidae) with plant based natural products -- Natural plant products as potential synthentic insecticide alternatives in developing countries of tropical african regions -- Traditional way of store grain pest control through bio-pesticides -- Botanical pesticides for organic farming and sustainable agriculture -- Management of crop diseases through botanical bio-pesticides -- an easiest arsenal of crop protection in organic agriculture -- Management of insect pests causing diseases in crops through biopesticides of insect sex Hormones origin -- Management of the pest of crops through insect sex pheromones -- Biological control of harmful forest insects: the biological efficiency of microbial insecticides and possibility of their application in forest ecosystems -- Role of natural enemies and bio-pesticides for sustainable management of major insect pests of legumes -- Conservative biological control: definitions, bases and practices -- Management of insect pests of crops through entomopathogenic nematodes -- Biological pest control in different crops using Trichogramma pretiosum -- Biological control of mite pests in organic farming -- Management of the diseases of crops through parasitoids bio-pesticides; family Eulophidae -- Management of Diatreae spp. through parasitoids -- Challenges in the applied use of parasitoids to control agricultural pests -- Microbial inoculants for insect pest management in organic agriculture -- Management of the diseases of crops through microbial bio-pesticides -- Quality control of fungal biocontrol agents with emphasis on Trichoderma -- Integrated insect pest management in major legume crops -- Integrated insect pest management of economically important crops -- IPM: concepts, practices and advances focused on organic crops -- Integrated pest management against arthropod pests of cannabis sativa in the United States of America -- Recent advances in the Integrated insect pest management strategies for controlling insect pest diseases at Morocco -- Biopesticides Weapons against agricultural mite pests -- Biotechnological trends in insect pests control strategy -- Challenges in the popularization of Biopesticides in organic farming -- Constraints and challenges in popularizing biopesticides -- Certification process and standards of organic farming -- Marketing and export potential of the organic products.
OCLC-licensed vendor bibliographic record.
Keywords: Natural pesticides; Organic farming; Crops -- Diseases and pests -- Biological control; SCIENCE / Life Sciences / Botany; TECHNOLOGY / Agriculture / General